2014
DOI: 10.1158/1078-0432.ccr-13-3296
|View full text |Cite|
|
Sign up to set email alerts
|

Niclosamide Inhibits Androgen Receptor Variants Expression and Overcomes Enzalutamide Resistance in Castration-Resistant Prostate Cancer

Abstract: Purpose Enzalutamide, a second-generation antiandrogen, was recently approved for the treatment of castration-resistant prostate cancer (CRPC) in patients who no longer respond to docetaxel. Despite these advances that provide temporary respite, resistance to enzalutamide occurs frequently. AR splice variants such as AR-V7 have recently been shown to drive castration resistant growth and resistance to enzalutamide. This study was designed to identify inhibitors of AR variants and test its ability to overcome r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
291
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(306 citation statements)
references
References 45 publications
8
291
1
6
Order By: Relevance
“…Furthermore, niclosamide induces apoptosis in acute myelocytic leukemia cells but spares cells from normal bone marrow (7). Thus, niclosamide is generally regarded as safe and efficient in many tumors, including colon cancer (5,14), breast cancer (3,4), and prostate cancer (8). In the present study, we evaluated the efficacy of niclosamide on human cancer cells in vitro.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, niclosamide induces apoptosis in acute myelocytic leukemia cells but spares cells from normal bone marrow (7). Thus, niclosamide is generally regarded as safe and efficient in many tumors, including colon cancer (5,14), breast cancer (3,4), and prostate cancer (8). In the present study, we evaluated the efficacy of niclosamide on human cancer cells in vitro.…”
Section: Discussionmentioning
confidence: 97%
“…In recent years, it has been suggested that niclosamide inhibited cancer growth and metastasis in epithelium-derived tumors, including prostate (8), lung (9,10), head and neck (11), and ovarian cancer (12,13). However, its effects on mesenchymal tumors (e.g., osteosarcoma) are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Niclosamide has been approved as anthelmintic against cestodes with well tolerated9 in humans for nearly 50 years 10. In recent years, niclosamide has been identified as a potential anti‐cancer agent in thyroid,11 renal,12 ovarian,13 lung,14 and prostate15 cancers. The downstream mechanism was also different in various cancers 9…”
Section: Introductionmentioning
confidence: 99%
“…Both in vitro and in vivo PCa tumour growth were reduced upon treatment with 74 and it has been suggested that it acts by promoting AR-V7 degradation via a proteasomedependent pathway [151] . Furthermore, the combination of niclosamide and enzalutamide resulted in significant inhibition of enzalutamide-resistant tumour growth, suggesting that niclosamide enhances enzalutamide therapy and overcomes enzalutamide resistance in CRPC cells [151] . A phase I study of niclosamide in combination with enzalutamide in men with CRPC is currently under investigation (NCT02532114).…”
Section: Seviteronel (5mentioning
confidence: 99%